2018
DOI: 10.1177/2309499018762616
|View full text |Cite
|
Sign up to set email alerts
|

Vascular injuries due to cerclage passer: Relevant anatomy and note of caution

Abstract: Purpose: The cerclage passer instrument was introduced for aiding percutaneous reduction in spiral femur fractures, thereby overcoming the risk of devascularization of the fracture ends commonly associated with traditional open cerclage wiring techniques. This may, however, predispose to iatrogenic vascular injuries owing to the proximity of the vessels and several other factors. We report four cases with femoral artery (superficial and deep) injuries caused by the cerclage passer in proximal femur and distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Injury to the SFA, deep femoral artery (DFA), or PA have been described as a result of broken sharp fragments or iatrogenic injuries such as external xation pins, plunging drill bits, medial plating, or cerclage wiring. These damages could give rise to immediate bleeding, late presented pseudoaneurysm, limb ischemia, or below knee amputation [1,5,[15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Injury to the SFA, deep femoral artery (DFA), or PA have been described as a result of broken sharp fragments or iatrogenic injuries such as external xation pins, plunging drill bits, medial plating, or cerclage wiring. These damages could give rise to immediate bleeding, late presented pseudoaneurysm, limb ischemia, or below knee amputation [1,5,[15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Especially during plate osteosynthesis or cerclage wiring, the formation of pseudoaneurysms, major lesions of the vessel wall, or vascular occlusions have been reported. This may even lead to severe consequences for the patient (Neubauer et al, ; Devendra et al, ). Apivatthakakul () showed that perforating arteries were interrupted in almost one quarter of percutaneous cerclage wiring simulated on anatomic specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In the worst case, the patients may lose their leg, or even their life (Neubauer et al, ). Therefore, knowledge about the course of the perforating arteries is essential during surgical approaches onto the body of the femur, for example, plate osteosynthesis (Farouk et al, ; Farouk et al, ; Neubauer et al, ), cerclage wiring (Apivatthakakul et al, ; Devendra et al, ), application of an Ilizarov apparatus (Paley, ; Goldstein et al, ), or the harvesting of free or pedicled perforator flaps (Yamamoto et al, ; Ahmadzadeh et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other concern with using the open cerclage wire technique is the risk of blood supply disruption by cerclage wires. Blood supply may be disrupted through the strangulation of blood vessels [28][29] and the contact between cerclage and the bone surface. The risk of vascular injury due to the cerclage passer was 1.59% in proximal femur shaft fractures and 7.14% in distal femur shaft fractures [28].…”
Section: Data Collectionmentioning
confidence: 99%